Information Security Analysis of Online Education Management System using Information Technology Infrastructure Library Version 3 - Michelle Cantika Pontoan; Jay Idoan SIhotang; Erienika Lompoliu (Universitas Bumigora, 2023)
The rapid development of information affects many aspects of human life. So that the field of information security becomes one aspect that must be considered. This study aims to measure the information security awareness and to improve daily operational activities of managing IT services effectively and efficiently. Salemba Adventist Academy has used the Wium Online Education Management System (WIOEM) online system, but in its implementation the security aspects of the system are not yet known. The Information Technology Infrastructure Library (ITIL) v3 framework which is globally recognized for managing information technology is broken down into five parts: Service Strategy, Service Design, Service Transition, Service Operation, Continual Service Improvement. This study focuses on Service Operations with 4 attributes, namely: Security, Privacy, Risk, and Trust. The data collection method used by the researcher was through observation in the form of a questionnaire in taking the number of samples to several students by taking population samples using the Lemeshow method. After the data were collected, the results of the ITIL indicator questionnaire are calculated based on the data security level. The results show that the Security indicator is Level 1, the Privacy indicator is level 3, the Risk indicator is level 3, and the Trust indicator is level 4 on the Data Security Level scale. This shows that the WIOEM system can be used properly according to user expectations and meets several levels of data security according to ITIL v3 framework.